Musculoskeletal injury risk after sport-related concussion: A systematic review and meta-analysis - McPherson, A. L.; Nagai, T.; Webster, K. E.; Hewett, T. E. (The American Journal of Sports Medicine, 2019)
Background: Clinical management of sport-related concussion typically involves a symptom checklist, clinical examination of mental status, and neurocognitive testing. However, recent studies have identified unresolved, impaired sensorimotor function after athletes return to sport. A review and meta-analysis of all current literature regarding risk of subsequent musculoskeletal (MSK) injury after concussion has yet to be published in the medical literature. Purpose/Hypothesis: To determine the odds that athletes will sustain MSK injury after concussion. It was hypothesized a priori that concussion would increase the risk for MSK injury. Study Design: Systematic review and meta-analysis. Methods: PubMed and Google Scholar were searched from January 2000 to November 2017. Reference lists of the included studies were manually searched. Two reviewers independently searched the literature for studies published in English that reported MSK injury after athletes returned to play following a concussion. Two independent reviewers completed data extraction using PRISMA guidelines and assessed study quality using the Quality Assessment Tool for Observational Cohort and Cross-Sectional Studies from the National Institutes of Health. Random effects meta-analyses were used to calculate odds ratio (OR) and incidence rate ratio (IRR) of MSK injury after concussion. The primary study outcome of interest was the number of athletes who sustained MSK injury after concussion. Results: Eight studies met inclusion criteria for meta-analysis. Meta-analysis results indicated that athletes who had a concussion had 2 times greater odds of sustaining a MSK injury than athletes without concussion (OR, 2.11; 95% CI, 1.46-3.06). In addition, athletes with concussion demonstrated a higher incidence of MSK injury after return to sport compared with nonconcussed athletes (IRR, 1.67; 95% CI, 1.42-1.96). Further analysis showed that both male and female athletes with concussion were at an increased risk of MSK injury compared with their respective same-sex, nonconcussed controls (OR > 1.56, P < .01). Conclusion: Based on the evidence of higher risk of MSK injuries after concussion, standard clinical assessments for athletes with concussion should include not only physical symptoms and cognitive function before return to sport but also neuromuscular risk factors associated with increased risk for MSK injuries.